The Effect of Changes in the Statutory Minimum Working Age on Educational, Labor and Health Outcomes - Sergi Jiménez-Martín; Judit Vall-Castello; Elena del Rey (Institute for the Study of Labor (IZA), 2015)
In this paper we explore the effects of a labor market reform that changed the statutory minimum working age in Spain in 1980. In particular, the reform raised the statutory minimum working age from 14 to 16 years old, while the minimum age for attaining compulsory education was kept at 14 until 1990. To study the effects of this change, we exploit the different incentives faced by individuals born at various times of the year before and after the reform. We show that, for individuals born at the beginning of the year, the probabilities of finishing both the compulsory and the post-compulsory education level increased after the reform. In addition, we find that the reform decreases mortality while young (16-25) for both genders while it increases mortality for middle age women (26-40). We provide evidence to proof that the latter increase is partly explained by the deterioration of the health habits of affected women. Together, these results help explain the closing age gap in life expectancy between women and men in Spain.
Keywords: J01; I26; I12; 330; minimum working age; policy evaluation; education; mortality